The Communist Party’s Ideological Apologetics in Suppresing Lithuanian National Resistance (1944–1953) - Bagušauskas , Juozapas Romualdas (Genocidas ir rezistencija, 2013)
Culture, spiritual and moral values are an inexhaustible source that for centuries revived the Lithuanian nation and gave it the strength to fight against all those who tried to destroy its statehood and suppress its aspirations for freedom. When Lithuania was incorporated into the USSR, the aim was to destroy everything that reminded us of the years of freedom and independence.
Keywords: soviet occupation; communist party; armed resistance; propaganda; communist ideology